Studies on the mineral nutrition of rice: XXIV. Absorption and redistribution of radiophosphate in the varieties L-45, Dourado Precoce and Penatie - Riera Acosta, A.V.; Carnauba, B.A.A.; Ciarelli, D.M.; Frazão, D.A.C.; Prado, H. do; Bergamaschi, H.; Mortatti, J.; Rossetto, R.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1983)
Root and leaf uptake of P32 was studied using upland rice cultivars, namely: L-45, Dourado Precoce and Penatie. Significant differences in absorption were observed among varieties. Except in the case of L-45 in_ tact plants were able to absorb more phosphorus than excised roots. The dual mechanism of absorption was observed, one operating within the range of 1-5 umoles in the external solution and the second one in that of 10² to 10(4) micromoles. When added to the solution of either monoammonium or diammonium phosphate urea increased foliar uptake. In the presence of the second source urea helped the transport to other organs of the plant. Highest rate of long distance transport was observed in the case of cv. Penatie, the lowest taking place in the variety Dourado Precoce.